PENGEMBANGAN BAHAN AJAR VIDEO ANIMASI MENGGUNAKAN APLIKASI PLOTAGON MATERI POLA HIDUP BERGOTONG ROYONG - Nur Azizah, Siti; Abdul Gani, Resyi; Destiana, Dita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Teaching materials are tools used to facilitate the learning process and improve students' understanding. However, at SDN Babakan Bogor, the teaching materials used have not been varied and digital-based. Therefore, in this learning, it is necessary to develop teaching materials so that the learning process becomes varied. The purpose of this research is to produce animated video teaching material products using the Plotagon Application on the material of Mutual Cooperation in class IV SDN Babakan Bogor. This research uses Research and Development (RnD) by applying the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique in this study used an instrument sheet in the form of a questionnaire. Product testing was carried out by media experts, linguists, and material experts. The results of the assessment from media experts 99%, language experts 100%, and material experts 91% which means it is very feasible to implement. And based on a limited trial conducted on class IV students as many as 20 people obtained a percentage value of 90% which means that the animated video teaching material using the Plotagon Application is very feasible to use in the learning process.